TEACHER STRATEGIES IN TEACHING READING COMPREHENSION AT THE EIGHTH GRADE STUDENT OF JUNIOR HIGH SCHOOL 1 UMBUNASI - Giawa, Delviani (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2022)
The strategies in teaching reading are very important, Related on the researcher preliminary study at Junior High School 1 Umbunasi, researcher found that most of students were active in teaching and learning process, and they are able to understand the reading text and answer the teacher's questions regarding the text of reading comprehension very well.The aims of this study was to find out what the teachers strategies in teaching reading comprehension and how the strategies applied by English teacher in teaching reading comprehension at the Eight Grade Student of Junior High School 1 Umbunasi. The method of this research was qualitative research. The result of the research show that there were some strategies used by the English teacher in teaching reading comprehension, namely memorizing, activating background knowledge, questioning and silent reading. Memorizing is a strategy for increasing the ability of students to memorize information. Activating background knowledge strategy help the students to understand the text with students prior knowledge. Questioning, the teacher able to know how far the students understand the text. And silent reading help the students to be more understand the reading text. Based on research finding, it can be concluded that memorizing, activating background knowledge, questioning and silent reading strategies were effective in teaching reading comprehension because can help student to comprehend the text. There for it is suggested to English teacher to apply this strategy in teaching reading comprehension, because this strategies can improve the quality of the English teacher in teaching English and students more interest and enjoy to learn.